Welfare gains from the adoption of proportional taxation in a general-equilibrium model with a grey economy: the case of Bulgaria's 2008 flat tax reform - Aleksandar Vasilev (Economic Change and Restructuring, 2015)
This paper provides a quantitative evaluation of the welfare effect of the introduction of proportional taxation in Bulgaria in 2008, an effect that operates through the grey economy channel. Using a general-equilibrium model, augmented with informal sector, a computational experiment is performed to evaluate the welfare gain from the adoption of proportional taxation. The lower effective tax burden in the new tax regime produces a relocation of people into the official sector, stimulates investment, and increases output and consumption. Finally, under the flat tax regime, the size of the informal sector is smaller, and quantitatively consistent with OECD (2009) and European Commission (2012) figures.
Additional information: this is the accepted version of the manuscript at the Economic Change and Restructuring
Keywords: D91; O41; 330; taxation; informal sector; labor reallocation; welfare gains